Do vocabulary, syntactic awareness, and reading comprehension in second language facilitate the development of each other in young children?. (December 2022) - Xie, Qiuzhi; Yeung, Susanna Siu-sze
Abstract: This study explored whether children's second language (L2) vocabulary, syntactic awareness, and reading comprehension contributed to the growth of each other. A total of 184 Chinese primary school children (91 girls) aged 8–10 years old in Hong Kong participated in the pre-test of this study. Among them, 88 were in Grade 3 and 96 were in Grade 4. One year later, 178 of these children also participated in the post-test. These children learned English as an L2 at school. They completed a series of English language tasks. The results from a cross-lagged panel model show that vocabulary predicted the growth of syntactic awareness and reading comprehension. Syntactic awareness predicted the growth of vocabulary and reading comprehension. Reading comprehension facilitated the growth of vocabulary, and it also predicted the growth of syntactic awareness in Grade 4 students but not in Grade 3 students. Implications for teaching children an L2 are discussed. Highlights: Vocabulary influenced the growth of syntactic awareness and reading comprehension. Syntactic awareness affected the growth of vocabulary and reading comprehension. Reading comprehension affected the growth of vocabulary. Reading comprehension affected syntactic awareness growth in Grade 4 students.